2020
DOI: 10.1096/fj.202001337r
|View full text |Cite
|
Sign up to set email alerts
|

ASIC1a regulates miR‐350/SPRY2 by N 6 ‐methyladenosine to promote liver fibrosis

Abstract: As a reversible scar repair reaction, liver fibrosis can be blocked or even reversed by proper intervention during its formation. Our work suggests that acid-sensitive ion channel 1a (ASIC1a) participates in liver fibrosis and presents a novel mechanism involving m 6 A modification and miR-350/SPRY2. We demonstrated that the expression of ASIC1a was significantly increased in liver tissue of patients with liver fibrosis and animal models of liver fibrosis, as well as PDGF-BB-induced activated HSC-T6. After dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…With regard to the effect of m6A methylation on the biological function of liver cells, existing studies have focused on the regulatory mechanism of genes and pathways ( Zhang C. et al, 2020 ; Cao et al, 2021 ). A study by Zhu Y. et al (2020) found that METTL3-mediated m6A methylation could be regulated by ASIC1a, which in turn affects the processing of miR-350, thus inducing the activation of HSCs and promoting the occurrence and development of LF. Unlike their studies, our study compared the difference in m6A methylation between the control and LF liver tissue, and confirmed that the m6A modification level changed significantly in LF.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the effect of m6A methylation on the biological function of liver cells, existing studies have focused on the regulatory mechanism of genes and pathways ( Zhang C. et al, 2020 ; Cao et al, 2021 ). A study by Zhu Y. et al (2020) found that METTL3-mediated m6A methylation could be regulated by ASIC1a, which in turn affects the processing of miR-350, thus inducing the activation of HSCs and promoting the occurrence and development of LF. Unlike their studies, our study compared the difference in m6A methylation between the control and LF liver tissue, and confirmed that the m6A modification level changed significantly in LF.…”
Section: Discussionmentioning
confidence: 99%
“…(an approximately half-fold) the levels of CaMKKß and ERK phosphorylation in a cell line of hepatic fibroblasts stimulated by high glucose and PDGF (Wang et al, 2019). Zhu et al (2020) showed a contribution of ASIC1a to increased ERK phosphorylation in the mechanism of liver fibrosis, as Pctx-1 treatment decreased the approximate 2-fold increase (without treatment) to a 1.5-fold increase. The same can be observed in ERK phosphorylated levels as the bands show a greater intensity for ERK-mediated NF-κB activation through ASIC1 in response to acidosis (although not quantified; Chen et al, 2016).…”
Section: Discussionmentioning
confidence: 88%
“…As an example, the activation of ERK via ASIC1a (downstream ASIC1a activation) has been analyzed in different pathological conditions (Chen et al, 2016;Sun et al, 2018;Zhu et al, 2020Zhu et al, , 2021. In addition, this pathway has also been linked to inflammation (Yu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…ASIC1a is expressed in rat hepatic stellate cells, suggesting that the formation of liver fibrosis is related to ASIC1a ( 112 ). Zhu et al ( 113 ) found that ASIC1a expression was significantly increased in liver fibrosis, and miR-350 was involved in the formation of liver fibrosis regulated by ASIC1a and activation of stellate cells. Further analysis proved that the mechanism of hepatic fibrosis caused by ASIC1a was via ASIC1a-mediated regulation of m6A to affect the processing and modification of miR-350, and participate in hepatic fibrosis through modulation of the PI3K/AKT and ERK pathways ( Fig.…”
Section: Pathology Of Asics In the Digestive Systemmentioning
confidence: 99%